Bequests and labor supply in Germany - Heiko Peters; Peter Schwarz (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2013)
Little is known on the effects of inheritances on the working behavior of heirs. Using panel data for Germany, we find behavioral responses that amount up to a 16% reduction in working hours for inheritances of one Mio Euro. For the majority of beneficiaries labor supply effects are, however, modest (owing to small amounts of inherited wealth). These results remain robust if we restrict the sample solely on those persons receiving an inheritance. Although more modest, higher inheritances promote a stronger adjustment in labor supply compared to small inheritances. In contrast to previous studies the partner does not adjust working hours and the full response takes place in the phase of the inheritance. Although negative income effects are present for all types of inheritances, behavioral responses are stronger if the heir receives liquid assets. The results depend, however, critically on the choice of the control group. – – Die Erbschaftsteuer gehört zu den kontrovers diskutierten Steuern. Eine der Rechtfertigungen von Erbschaftsteuern weist auf die negativen Arbeitsangebotseffekte in Folge einer Erbschaft hin. Zum Arbeitsangebotsverhalten des Erben existieren jedoch nur wenige empirische Untersuchungen. Mit Hilfe eines Paneldatensatzes für Deutschland finden wir bei Erbschaften von einer Million Euro eine Reduktion des Arbeitsangebots von bis zu 16%. Je höher die Erbschaft ausfällt, desto grösser fällt auch die Reduktion der Arbeitsstunden aus. Für einen Grossteil der Erben sind die Arbeitsangebotsreaktionen aufgrund der niedrigen Erbschaftssumme aber moderat. Die Ergebnisse ändern sich qualitativ nicht, wenn das Sample lediglich auf Erben restringiert wird. Im Gegensatz zu vorangegangenen Untersuchungen passt der Lebenspartner des Erben sein Arbeitsangebot aber nicht an. Zudem finden wir stärkere Anpassungsreaktionen bei liquiden im Vergleich zu illiquiden Erbschaften. Dieses Resultat hängt jedoch stark von der Auswahl der Kontrollgruppe ab.
Keywords: H24; J22; 330; inheritance; labor supply; income effect; liquid assets